A Case-Law Analysis of The Commercial Enterprise of The Sole Proprietor and Its Co-Relation to The Matrimonial Community Property - Mateeva, Ekaterina (Yearbook of the Law Department, 2020)
The present research puts the focus upon the development of case law regarding one of the fundamental aspects of matrimonial property relations of the sole proprietor (SP) whenever the statutory regime of community of property is applicable, in particular the co-relation between the matrimonial community property and the commercial enterprise of the spouse – SP. The article focuses on case law development regarding the substantive legal requirements to cancel the effect of the presumption of joint contribution pursuant to art. 21, s. 1, 3 of the Family Code 2009 concerning property rights acquired by the SP during his or her marriage to be included into his or her commercial enterprise. Special regard is attributed to the shift in recent case-law since the entry into force of the present Family Code in 2009 on the origin of money used to acquire property rights, that become personal property of the spouse-SP pursuant to art. 22, s. 3 of the Family Code. Moreover, attention is being credited to the general purpose of the requirement to include property rights into the enterprise of the spouse-SP and its significance for the acquisition of personal property pursuant to art. 22, s. 3 of the Family Code.